SPIRITUAL BACKGROUND OF SLOVAK NATURE POETRY - Gavura, Ján (Bohemica Olomucensia, 2021)
The paper provides a survey of selected Slovak poets of the 20th and 21st centuries who produce nature poetry containing numerous spiritual elements. In fact, one of the paper's conclusions is that spiritual and natural aspects are intertwined to such an extent that it is impossible to state whether the poems are spiritual or natural in their substance and, subsequently, whether the other aspect just develops the basis. Slovak poetry of recent decades brings examples in which nature plays a decisive role in expressing spirituality and morality, however, individual examples show that there are more ways of - and also reasons for - using natural motifs in poetry. During the communist era in Czechoslovakia, nature represented for poets a safe space, an exile, and provided means of expression that allowed them to speak about ethics without compromising themselves with politics. For some authors, nature was a divine manifestation of God and was treated with utmost respect. The nature with its natural laws and order is set as an example for human beings in their pursuit of happiness and even salvation.
Keywords: Nature poetry; Slovak poetry of 20th and 21st centuries; spirituality